Coronary slow flow is associated with a worse clinical outcome in patients with Takotsubo syndrome. Issue 12 (10th January 2020) - Montone, Rocco A; Galiuto, Leonarda; Meucci, Maria Chiara; Del Buono, Marco Giuseppe; Vergni, Federico; Camilli, Massimiliano; Sanna, Tommaso; Pedicino, Daniela; Buffon, Antonino; D'Amario, Domenico; Giraldi, Luca; Trani, Carlo; et al.
Abstract : Objective: Patients with Takotsubo syndrome (TTS) present an acute microvascular dysfunction that leads to an impaired myocardial perfusion and, in more severe forms, an impaired epicardial flow. However, clinical relevance of a delayed coronary flow, the coronary slow flow (CSF), has never been investigated. We studied the prognostic value of CSF occurring in the acute phase of TTS. Methods: This cohort study prospectively evaluated patients with a diagnosis of TTS. CSF was defined as angiographically non-obstructive coronary arteries with thrombolysis in myocardial infarction-2 flow. The incidence of overall mortality and major adverse cardiovascular events (MACEs), defined as the composite of TTS recurrence, cardiac rehospitalisation, cerebrovascular events and mortality, was assessed at follow-up. Results: We enrolled 101 patients (mean age 71.0±11.1 years, 86 (85.1%) female); CSF occurred in 18 (17.8%) patients. At admission, patients with CSF presented more frequently with Killip class III/IV, moderate-to-severe left ventricle systolic dysfunction and right ventricle dysfunction. During the index admission, patients with CSF had a higher rate of intrahospital complications (12 (66.7%) vs 28 (33.7%), p=0.01). At long-term follow-up, patients with CSF had a significantly higher occurrence of overall mortality (9 (50%) vs 19 (22.9%), p=0.011), mainly due to non-cardiac causes (89.3%), and a higher rate of MACE (10 (55.5%) vs 27 (32.5%), p=0.06). At multivariable Cox regression, CSF was independently associated with death from any causes. Conclusions: Patients with TTS presenting with CSF have a worse clinical presentation with a higher rate of intrahospital complications and a poor long-term clinical outcome.